The influence of sighing respirations on infant lung function measured using multiple breath washout gas mixing techniques - Vukcevic, D.; Carlin, J.; King, L.; Hall, Graham; Ponsonby, A.; Sly, P.; Vuillermin, P.; Ranganathan, S. (2015)
There is substantial interest in studying lung function in infants, to better understand the early life origins of chronic lung diseases such as asthma. Multiple breath washout (MBW) is a technique for measuring lung function that has been adapted for use in infants. Respiratory sighs occur frequently in young infants during natural sleep, and in accordance with current MBW guidelines, result in exclusion of data from a substantial proportion of testing cycles. We assessed how sighs during MBW influenced the measurements obtained using data from 767 tests conducted on 246 infants (50% male; mean age 43 days) as part of a large cohort study. Sighs occurred in 119 (15%) tests. Sighs during the main part of the wash‐in phase (before the last 5 breaths) were not associated with differences in standard MBW measurements compared with tests without sighs. In contrast, sighs that occurred during the washout were associated with a small but discernible increase in magnitude and variability. For example, the mean lung clearance index increased by 0.36 (95% CI: 0.11–0.62) and variance increased by a multiplicative factor of 2 (95% CI: 1.6–2.5). The results suggest it is reasonable to include MBW data from testing cycles where a sigh occurs during the wash‐in phase, but not during washout, of MBW. By recovering data that would otherwise have been excluded, we estimate a boost of about 10% to the final number of acceptable tests and 6% to the number of individuals successfully tested.